In a previous MO question, the OP asks a proof for $\det_{1\leq i,j\leq n}\left(\binom{i}{2j}+\binom{-i}{2j}\right)=1$. Subsequently, Gjergji Zaimi generalized the problem to $$\det_{1\le i,j\le n}\left( \binom{x_i}{2j}+ \binom{-x_i}{2j}\right)=\prod_{i=1}^n x_i^2 \prod_{i<j} (x_j^2-x_i^2) \prod_{j=1}^n \frac{2}{(2j)!}.$$ Let's define $$\Psi_n:=\prod_{i=1}^n x_i^2 \prod_{i<j} (x_j^2-x_i^2) \prod_{j=1}^{\mathbf{n+1}} \frac{2}{(2j)!}.$$ Recall the elementary symmetric functions $e_k=e_k(x_1^2,\dots,x_n^2)$. Now, I would like ask:

Question 1. Is it true that there exist positive integers $a_0, a_1, \dots, a_n$ such that $$\det_{1\le i,j\le n}\left( \binom{x_i}{2j+2}+ \binom{-x_i}{2j+2}\right)= (a_0+a_1e_1+\cdots+a_{n-1}e_{n-1}+a_ne_n)\cdot\Psi_n.$$ Question 2. What are these coefficients $a_0, a_1, \dots, a_n$?

NOTE. For any $n$, we observe that $a_n=1, a_{n-1}=11, a_{n-2}=661, a_{n-3}=151451$. These sequence does not appear on OEIS.


1 Answer 1


Let $M$ be the matrix in question. The entry $M_{ij}$ is of the form $\frac{2x_i^2}{(2j+2)!}p_j(x_i)$ for some even polynomial $p_j$ of degree $2j$. After factoring out the $2x_i^2$ terms from each row and the $\frac{1}{(2j+2)!}$ terms from each column, we are left with the matrix $(p_j(x_i))_{i,j=1}^n$. This can be column reduced to a matrix $P$ with rows $(x_i^2+a_1,x_i^4-a_2,x_i^6+a_3,\dots)$, where $a_1=11$, $a_2=661$, $a_3=151451$, etc. It remains to show that $\det P$ is $(a_ne_0+a_{n-1}e_1+\cdots+a_1e_{n-1}+e_n)\prod_{i<j}(x_j^2-x_i^2)$.

$P$ breaks into the sum of a Vandermonde matrix $V$ in the indeterminates $x_i^2$ and a rank-$1$ matrix $uv^\top$, where $u=(1,\dots,1)^\top$ and $v=(a_1,-a_2,a_3,\dots,(-1)^{n-1}a_n)^\top$. By the matrix determinant lemma, $\det P=\det V(1+v^\top V^{-1} u)$. Since $\det V=e_n\prod_{i<j}(x_j^2-x_i^2)$, it suffices to show that $V^{-1}u=(e_{n-1},-e_{n-2},\dots,(-1)^{n-1} e_0)^\top/e_n$. Indeed, the $i$th entry of $V(e_{n-1},-e_{n-2},\dots,(-1)^{n-1} e_0)^\top/e_n$ is $$(e_n-e_n+x_i^2e_{n-1}-\cdots\pm x_i^{2n}e_0)/e_n=(e_n\pm(x_i^2-x_1^2)\cdots(x_i^2-x_n^2))/e_n=1.$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.